Filipino children's favorite stories - Romulo, Liana (Periplus, 2000)
"A collection of well-loved myths and tales from the Philippines. Many of the tales have been told by mothers to children over the centuries and cover classic childhood themes, such as the forces of good versus evil, children versus adults, the weak versus the strong, and others.While some of the stories have been retold and printed in many variations, others have never been published before"--Jacket.